2007
DOI: 10.1002/art.22370
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α acceleration of inflammatory responses by down‐regulating heme oxygenase 1 in human peripheral monocytes

Abstract: Objective. To examine the interaction between heme oxygenase 1 (HO-1), a stress-induced antiinflammatory protein, and tumor necrosis factor ␣ (TNF␣) in human peripheral blood monocytes. Heme oxygenase (HO) is an enzyme that converts heme into carbon monoxide, Fe 2ϩ , and biliverdin (1,2). HO-1, an inducible isozyme of HO, is a 32-kd heat-shock protein that is expressed in response to a variety of noxious stimuli, including heavy metals, hyperoxia, hypoxia, endotoxins, and hydrogen peroxide (1,2). Evidence sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…We further studied the transcription activity for HO-1 expression in PMA-treated U937 cells that had been transfected with a luciferase-expressing plasmid encoding the MARE EN1 region (pHO-1(-4.5k)) or with a plasmid lacking the MARE site (pHO-1(-4.0k)). (21) LPS attenuated luciferase activity in cells transfected with pHO-1 (-4.5k) but not in cells transfected with pHO-1(-4.0k), suggesting that the effect of LPS depended on the MARE (Fig. 4C).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We further studied the transcription activity for HO-1 expression in PMA-treated U937 cells that had been transfected with a luciferase-expressing plasmid encoding the MARE EN1 region (pHO-1(-4.5k)) or with a plasmid lacking the MARE site (pHO-1(-4.0k)). (21) LPS attenuated luciferase activity in cells transfected with pHO-1 (-4.5k) but not in cells transfected with pHO-1(-4.0k), suggesting that the effect of LPS depended on the MARE (Fig. 4C).…”
Section: Resultsmentioning
confidence: 95%
“…Protein expression levels were determined by SDS-PAGE and subsequent immunoblotting as previously described. (21) For several experiments, cytoplasmic and nuclear extracts were prepared from cells with NE-PER Nuclear and Cytoplasmic Extraction Reagents (Pierce Biotechnology, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α, a proinflammatory and pro-apoptotic cytokine, has been shown to modulate HO-1 expression. In a recent study, Kirino et al have demonstrated that TNF-α suppresses HO-1 expression in human peripheral monocytes via increased mRNA degradation [27]. Since reduced HO-1 expression is associated with increased cell death, we investigated whether IL-18 modulates HO-1 expression in EC.…”
Section: Il-18 Inhibits Ho-1 Mrna Expressionmentioning
confidence: 93%
“…A 4.5 kb of the 5'-flanking region of human HO-1 was amplified from human genomic DNA using the sense primer 5′-ggt acc TTG GGC TTG TCT TCC TTG CT-3′ and the antisense primer 5′-ctc gag CATCCGGCCGGTGCTGGGCTCGT-3′ and cloned into the pCR2.1-TOPO vector, digested with Kpn I and Xho I, and subcloned into the pGL3-Basic reporter vector (pHO-1-Luc) as previously described [27]. EC were transiently transfected with pHO-1-Luc (2 µg), and 24 h later, treated with IL-18 for 12 hours.…”
Section: Transient Cell Transfections and Reporter Assaysmentioning
confidence: 99%
“…The thiol-reactive auranofin modifies Cys-179 in beta subunit of inhibitory κB kinase (IKK), which results in the blockade of inhibitory κB-α (IκB-α) phosphorylation and degradation [6,7]. Consequently, auranofin attenuates the transcriptional activity of NF-κB and downregulates the expression of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β).Heme oxygenase-1 (HO-1), which suppresses an inflammatory response, is also associated with the pharmacological property of auranofin in rheumatoid arthritis [14,16]. In the previous study, we found that auranofin induced HO-1 via the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) in human synovial cells and THP-1 monocytic cells.…”
mentioning
confidence: 99%